2019
DOI: 10.1039/c9cy01428d
|View full text |Cite
|
Sign up to set email alerts
|

Ceria–zirconia encapsulated Ni nanoparticles for CO2 methanation

Abstract: Preparing Ni catalysts on ceria–zirconia via colloidal Ni nanoparticle encapsulation yields excellent particle size control, superior catalytic activity, and enhanced stability compared to conventional impregnation techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 59 publications
(69 reference statements)
0
11
0
Order By: Relevance
“…suppressed the sintering of Ni by encapsulating colloidal Ni NPs into the mesoporous SiO 2 support directly, in which the particle size remained almost unchanged after 70 h reaction. In addition, they further revealed that Ni@CZ catalysts, synthesized by sol‐gel protocol, presented much higher activity and better stability, because that ceria‐zirconia support can encapsulate Ni NPs and prevent their contact [18] . Zhang [19] et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…suppressed the sintering of Ni by encapsulating colloidal Ni NPs into the mesoporous SiO 2 support directly, in which the particle size remained almost unchanged after 70 h reaction. In addition, they further revealed that Ni@CZ catalysts, synthesized by sol‐gel protocol, presented much higher activity and better stability, because that ceria‐zirconia support can encapsulate Ni NPs and prevent their contact [18] . Zhang [19] et al.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they further revealed that Ni@CZ catalysts, synthesized by solgel protocol, presented much higher activity and better stability, because that ceria-zirconia support can encapsulate Ni NPs and prevent their contact. [18] Zhang [19] et al concluded that the high stability of LaNi 0.95 Co 0.05 O 3 /MCF catalyst was due to the confinement effect of 3-dimensional mesostructured cellular foam silica support, and Ni NPs were physically isolated by the neighboring La 2 O 3 species.…”
Section: Introductionmentioning
confidence: 99%
“…The deposited coke on the spent 10Ni-10ZrO2/Al2O3 (SI) catalyst was found not only in the lesser amount but also in an easier removal characteristic compared to other catalysts. Considering the O2-TPD and the H2-TPR results, the reason for this easier removal is attributed to the high amount of oxygen mobility accompanied with the greater interaction between Ni and the ZrO2-Al2O3 composite that enhances both the Ni distribution (resulting in smallest Ni particle sizes) and pathway of the vacancy sites for the oxygen transfer from ZrO2 in ZrO2-Al2O3 through coke on the Ni surface in the CRM process [27,28,49]. The coke deposition on the spent catalysts of CSCRM was determined by TPO results (Figure 9).…”
Section: Coke Depositionmentioning
confidence: 99%
“…48 Previous studies revealed that the nature of the support and the synthesis method have a strong impact on the observed Ni particle shapes. 49,50 Another primary characterisation tool for the Ni-PSD of Ni/ZrO 2 catalysts is H 2 chemisorption. While this method allows estimating an averaged diameter, the exact ZrO 2 morphology can also strongly impact the average Ni size.…”
Section: Catalyst Characterisationmentioning
confidence: 99%